(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
To solve ever-changing crimes, law enforcement organisations must be adaptable. In the fieldof criminal data analysis, data analytics has shown to be an effective deterrent. This strategy has benefiteda number of nations, including the United States of America. The Indian government has also made stepsto adopt data analytics in order to help in crime prevention. We utilised R Studio to undertake dataanalysis on the crime dataset supplied by the Police Department in this article. Every country strives toimprove the quality of life for its residents by ensuring the safety and security. India‟s recommendationson crime prevention integrate and expand on years of experience and trials in dealing with these issues.Using realistic, tangible ways that are considerably different from, and less expensive than, repressiveand deterrent attitudes and responses, governments may establish safer communities.